Biomass Convertion For Renewable Alternative Energy - Hafiizh Prasetia; Nova Annisa; Lenalda Febriany Santosa (Green Visioneers, 2018)
Biomass is an organic material produced through a process of photosynthesis and can be used as an energy source. In general, biomass used as alternative fuel is considered because it has economic value which is relatively cheap because it comes from waste around the community. In addition, biomass is one way to reduce the waste problem in the community. Such as agricultural, livestock and other wastes where the waste is not properly managed and can have adverse effects on the environment. Energy conversion is a change of energy from one to another, so conversion of this biomass energy converts a biomass energy into another energy in which the raw material used comes from waste. The conversion of biomass energy is very beneficial for many sectors. Such as coconut husk that can be converted into thermal energy and beneficial to the crafters of anchovy and like animal feces, especially cattle that can be converted into thermal energy or biogas and can be beneficial to the surrounding community. Therefore, the conversion of this biomass energy while providing a positive impact in addition to the community also has a positive impact on the environment for now as well as years to come.